Review Plaza de los Lobos 1968-1977: Plaza de los Lobos 1968-1977. Memorias de estudiantes antifranquistas de la Universidad de Granada. - Frápolli, María José (Analysis. Journal of Philosophical Research, 2024)
Thirteen alumni from the University of Granada share their memories of those turbulent years when the end of the Franco's regime was in sight, yet the structures of the dictatorship were still in place. The book includes a prologue by former rector Dª Pilar Aranda and, as an epilogue, the speech given by the current rector, D. Pedro Mercado—then Vice-Rector for Institutional Policy and Planning—at the inauguration of the plaque that the UGR placed on the building on Duquesa Street on June 2, 2022.